On the mechanics of edge chipping from spherical indentation - Chai, Herzl (International journal of fracture, 2011)
Edge chipping is a basic failure mode in brittle materials which is dictated by a wealth of material and geometric variables. Here we examine the effect of indenter bluntness on chipping load and chip dimensions. Soda-lime glass and YTZP plates are subject to surface-normal loading near an edge by a W/C ball or a Vickers tool. The ball radius r is varied from 0.2 to 8.7 mm while the indent distance h is varied from several millimeters down to a few microns. Although cone cracks are a common feature under spherical indentation, the chipping event is dominated by median-radial cracks formed under the contact. The fracture behavior is characterized by a “large” indent distance regime where the median cracks progress stably up to chipping and a “small” one where they grow unstably to form a chip once initiated. Closed-form relations for chipping load P F under spherical indentation is developed with the aid of the test data and non-dimensional arguments. While in the “large” distance regime P F is proportional to h 3/2 irrespective of tool bluntness, in the “small” regime P F is proportional to r 1/2 h 3/4 . Interestingly, the chip dimensions are virtually independent of ball radius, varying linearly with h . Beyond relevance to structural integrity, the chipping test facilitates a simple means for determining fracture toughness K C as well as the load needed to initiate median cracks in opaque brittle materials. An attempt is made to extend the static analysis to low-velocity impact. The results show that the damage formed during the fracture process has a major influence on dynamic chipping.